Effect of oxidizing agents on the treatment of a Colombian lead ore through hydrometallurgical alternative processes - Borda, Johana; Torres, Robinson; Salamanca, Ivan (Journal of Mining and Metallurgy, Section B: Metallurgy, 2024)
The lead recovery from a Colombian ore of low metallic richness was studied, the research was developed in carboxylic media at ambient conditions. A preliminary chemical treatment was necessary to improve the metal extraction. For this, two hydrometallurgical treatments were used: i) pneumatic agitation with ozone injection and ii) mechanical agitation with hydrogen peroxide dosing.  Lead extractions from the pretreated ore were similar to those from the leach without pretreatment. This situation attributed the dissolution of lead to the complexing action of the carboxylic agent rather than to the effect of the pretreatments. Direct dosing of peroxide to the citrate leach achieved extractions of 50% of the metal, improving by more than 30% that was achieved by leaching without the oxidizing agent addition. The leaching of the ore with 0.5M citrate and pH 4.5 yielded a redox potential of 926 mV, which ensured the high activity of the electrons in the chemical reaction and therefore the lead ions dissolution.